2017
DOI: 10.1371/journal.pone.0168633
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bile Salts and the Development of Necrotizing Enterocolitis in Preterm Infants

Abstract: BackgroundIntestinal bile salts (BSs) may be implicated in NEC development. We hypothesized that fecal BS levels are higher in preterm infants at risk for NEC.MethodsWe compared the composition and concentration of fecal BSs in ten preterm infants who developed NEC (Bell’s Stage ≥ II) with twenty matched control infants without NEC. Conjugated and unconjugated fecal BSs were measured after birth (T1) and twice prior to NEC (T2, T3). Data are presented as medians and interquartile ranges.ResultsGA and BW were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…While exposure to varying levels of hydrophobic BAs has been shown to increase proliferation of cells in esophageal reflux and Barrett's esophagus [58][59][60] , cytotoxic effects of intermittent exposure to BAs in neonatal intestine has not been published. While previous research reported a statistically significant increase in total unconjugated BAs in NEC patients compared to controls 48 , we did not observe a statistically significant increase in mean BA quantity for any individual BA, BA group, or total BAs. However, our study differed from theirs in that we used matched pairs, analyzed more samples per subject, looked at slightly different outcomes, and had lower power due to a smaller sample size and correcting for multiple comparisons (that is, we required a lower p-value for "statistical significance").…”
Section: Discussioncontrasting
confidence: 99%
“…While exposure to varying levels of hydrophobic BAs has been shown to increase proliferation of cells in esophageal reflux and Barrett's esophagus [58][59][60] , cytotoxic effects of intermittent exposure to BAs in neonatal intestine has not been published. While previous research reported a statistically significant increase in total unconjugated BAs in NEC patients compared to controls 48 , we did not observe a statistically significant increase in mean BA quantity for any individual BA, BA group, or total BAs. However, our study differed from theirs in that we used matched pairs, analyzed more samples per subject, looked at slightly different outcomes, and had lower power due to a smaller sample size and correcting for multiple comparisons (that is, we required a lower p-value for "statistical significance").…”
Section: Discussioncontrasting
confidence: 99%
“…Five to six days before NEC onset, fecal bile salt levels were significantly higher compared with age matched controls. The slower decay of fecal BS supports a potential role for altered BS metabolism or transport in NEC development (56). This difference in trajectory may be intrinsic to host phenotype, but is also linked to more modifiable factors including the gut microbiota, which has been previously shown to alter the expression of bile salt transporters (57).…”
Section: Non-microbial Biomarkersmentioning
confidence: 81%
“…Within this context, their contribution to NEC pathophysiology has recently been studied. In the week preceding NEC manifestation, fecal unconjugated BA levels were found to be higher in preterm infants, eventually developing NEC compared with gestation-matched controls [10]. More precisely, the intraluminal accumulation of conjugated BAs resulted in intestinal epithelial damage, similar to the histopathological findings in NEC [11].…”
Section: Introductionmentioning
confidence: 54%
“…In addition, the increased expression of the apical sodium-dependent bile acid transporter (ASBT) in the terminal ileum, a protein involved in the uptake of conjugated BAs into the enterocytes, was reported in preterm infants with NEC and in an experimental NEC model with rodents which correlated with the location of intestinal damage, suggesting increased BAs uptake by enterocytes [13,14]. Consequently, high concentrations of intraluminal BAs resulted in their accumulation within enterocytes, with concomitant enterocyte damage [10]. Moreover, a decreased expression of the ileal bile acid-binding protein (IBABP) was seen in the terminal ileum of rats in an experimental NEC model, suggesting insufficient transport from the apical to the basolateral side of enterocytes with consequent BAs accumulation within the enterocytes [14].…”
Section: Introductionmentioning
confidence: 99%